Simultaneous Bilateral Extensor Mechanism Disruptions: More Than Double the Trouble? - Seifert, Christina; Vokes, Jordan; Roberts, Aaron; Gorczyca, John; Judd, Kyle (The Journal of Knee Surgery, 2019)
Simultaneous bilateral extensor mechanism disruption (BEMD) is a rare condition, for which the relationship between comorbid conditions, complications, and clinical outcomes has not been well defined. We hypothesized that patients with BEMD would have more comorbidities, more repair failures, and worse clinical outcomes compared with patients with unilateral extensor mechanism disruption (UEMD). We performed a retrospective review of all adult patients seen at our institution for either a quadriceps or patellar tendon rupture between 2012 and 2017. Statistical analysis was conducted using Student's t-tests and Fisher's exact tests. Significance was defined as p < 0.05. Fourteen patients with BEMD and 221 patients with UEMD were included for comparison. The average length of follow-up was 268 days. Patients with BEMD had higher body mass indexes and higher American Society of Anesthesiologists scores than patients with UEMD. They also had worse Patient-Reported Outcomes Measurement Information System physical function scores, nearly four times the length of stay, and three times the rate of repair failures as patients with UEMD. At final follow-up, all 14 patients in the BEMD group were ambulatory and 9 of the 10 patients who were working prior to injury had returned to work. Simultaneous BEMD are rare injuries, occurring in only 6% of the current series. When treating these patients, orthopaedic surgeons should have a heightened awareness that they have more comorbidities, more failures, and worse functional outcomes than their unilateral counterparts.
Keywords: extensor mechanism disruption; PROMIS score; bilateral